Squaring the Circle : the Extreme Left and the Labour Party - Jeremy Tranmer (Revue LISA)
Although the extreme left has often managed to mobilise large numbers of people in demonstrations and has had a significant influence in the trade union movement, it has always faced serious obstacles preventing it from becoming a major force, one of the most important of which has been the strength of the Labour Party. For much of its history, the extreme left has hesitated between being a pressure group, aiming to exert influence over Labour, and a political entity in its own right. This hesitation reveals a great deal about the weakness of the extreme left within the British left as a whole. Even though most sections of the far left have put an end to their political schizophrenia by opting for an independent stance, this decision has not led to a change in its fortunes.